5PSQ-082 Regulatory news related to valproate derivatives: a real-life retrospective study. (March 2019) - Charreteur, R; Chapet, N; Mathieu, B; Seron, A; Castet-Nicolas, A
Abstract : Background: Following Pharmacovigilance Risk Assessment Committee (PRAC) recommendations based on meta-analysis, the European Commission has validated since the 31 May 2018, new restrictions in the use of valproate derivatives (VD) related to teratogenicity. VD must not be prescribed to women of childbearing age (WCA) unless the conditions of a new pregnancy prevention programme are met. In France since 2015, The National Agency for the Safety of Medicines and health products (ANSM) recommended to WCA the use of an effective contraception and an annual care agreement (CA). Purpose: The aim of this study was to evaluate the conformity of prescriptions of VD in WCA at a university hospital. Material and methods: We performed a retrospective analysis of all prescriptions between June 2017 and August 2018 comprising VD to women aged between 15 to 49 years. Data were extracted from the electronic prescribing and medical record software. Analysis criteria were the presence or mention of a CA and a contraceptive method in the medical record, together with pharmaceutical validation status. Results: Eighty-six patients were prescribed VD, corresponding to 116 stays. The mean age was 37.4 years. A contraceptive method was mentioned in 28.8% of stays. A CA was found or mentioned in the medical file in 28.0% of cases. Pharmacists requested it in 39.8% of prescriptions and obtained it in 42.5% of cases, within a median time of 2.5 days. Eighty per cent of CA were acquired during hospitalisation, at the request of the pharmacist in 70% of cases. A CA was found in 30% of validated prescriptions. Seventy-five per cent of prescriptions were validated in the absence of CA. Age stratification did not show any influence on the presence of CA. To our knowledge, this is the first study of this magnitude in a university hospital in France. If the results suggest a low compliance to the ANSM recommendations, this study will serve as a working support to establish corrective actions. Conclusion: While efforts must be made to comply with regulations, the hospital pharmacist seems to play a key role in promoting compliance to guidelines. However, a new awareness of healthcare providers to the appropriate use of VD is urgent to establish. References and/or acknowledgements: No conflict of interest.